Britain's Subjects, Ireland's Guests; West African Students at Trinity College Dublin and in Ireland 1930-1970 - Opare, Gabriel Nkansah (Trinity College Dublin. School of Social Sciences & Philosophy. Discipline of Sociology, 2026)
This dissertation extends the study of colonial students beyond Britain to Ireland, examining Nigerians and other West Africans at Trinity College Dublin between 1930 and 1970. It reconstructs their educational trajectories, associational and intellectual lives, as well as encounters with race, in a context shaped by both imperial authority and Ireland's own colonial past. Five original papers form the structure. Paper 1 explores how medical school, family, postwar/colonial, gender, and missionary archives can be used to navigate around archival silences when reconstructing the histories of overlooked colonial students. Paper 2 analyses the Association for Students of African Descent as a site where colonial migrants in Dublin forged pan-African solidarities and articulated decolonial politics, while Paper 3 examines their participation in the University Philosophical Society, focusing on Egbert Udo Udoma's 1942 presidential address, to show how Irish debating forums became arenas for anti-imperial discourse and the cultivation of a West African intelligentsia. Paper 4 turns to the 1964 Fadipe affair, in which the assault of a Nigerian medical student prompted public controversy. It situates the episode within longer histories of racialisation, belonging and postcolonial negotiation in Ireland. Together, the dissertation demonstrates that Ireland was not peripheral but central to the history of colonial students, providing training, support networks and careers while also exposing the racial hierarchies and political conflicts of the mid-twentieth century. It shows that West African students in Ireland were not passive recipients of colonial education, but rather agents who negotiated identity, leadership, and decolonisation within an institution and a society marked by the legacies of Empire.
APPROVED
Keywords: Trinity College Dublin; decolonisation; African-Irish; race relations; colonial students